A methodology to assess China's building energy savings at the national level: An IPAT–LMDI model approach. (1st February 2017) - Ma, Minda; Yan, Ran; Du, Yongjie; Ma, Xianrui; Cai, Weiguang; Xu, Pengpeng
Abstract: National building energy savings (NBES) plays an essential role in policymaking of China's building energy–efficiency (BEE) work. Numerous factors, such as technological progress and users' behavior, affect NBES while most of them are unquantifiable. One missing possibility along this direction is that there is currently no method to calculate China's NBES by summarizing all driving factors. To arrive at a solution, we proposed a concept of comparable building energy consumption per unit area and a method of China's NBES calculation based on an extended version of IPAT model (I = PAT, I = Human Impact, P = Population, A = Affluence, T = Technology) and LMDI decomposition (Logarithmic Mean Divisia Index, LMDI). Calculation revealed that China's NBES in "The 10th Five–Year Plan" period (2001–2005), "The 11th Five–Year Plan" period (2006–2010), and the first four years of "The 12th Five–Year Plan" period (2011–2014) was 165, 158, and 127 million tce, respectively. Based on these calculation results, we checked NBES data then successfully proved the validity of this calculation method. Furthermore, after comparing the calculated NBES with the official planned NBES, we found that China surpassed its BEE targets. In the third stage of China's BEE work (2006–2015), the implementation of BEE policies obtained good results. Highlights: We firstly put forward an IPAT–LMDI model–based China's NBES calculation method. China's NBES was 165 million tce in 2001–2005. China's NBES was 158 million tce in 2006–2010. China's NBES was 127 million tce in 2011–2014. We evaluated the effectiveness of China's BEE policies based on NBES data.